Pyrochlore glass‐ceramics fabricated via both sintering and hot isostatic pressing for minor actinide immobilization. Issue 10 (3rd April 2020) - Zhang, Yingjie; Zhang, Zhaoming; Wei, Tao; Kong, Linggen; Kim, Young J.; Gregg, Daniel J.
Abstract: Pyrochlore glass‐ceramics (GCs) have been investigated with samples fabricated via both sintering and hot isostatic pressing (HIPing) of a mixed oxide precursor. It has been demonstrated that sintering at 1200°C in air is necessary to obtain well‐crystallized pyrochlore crystals in a sodium aluminoborosilicate glass through a one‐step controlled cooling. The crystallization, structure, and microstructure of Eu2 Ti2 O7 pyrochlore as the major phases in residual glass were confirmed with X‐ray diffraction (XRD), scanning electron microscopy‐energy dispersive spectroscopy, transmission electron microscopy, and Raman spectroscopy. The structures of major Eu2 Ti2 O7 pyrochlore and minor [Eu4.67 O(SiO4 )3 ] apatite in both sintered and HIPed samples were refined using synchrotron XRD data. While the processing atmosphere did not appear to affect the cell parameter of the main pyrochlore phase, very small volume expansion ( 0.3%) was observed for the minor apatite phase in the HIPed sample. In addition, static leaching of the HIPed sample confirmed that pyrochlore GCs are chemically durable. Overall, pyrochlore GCs prepared via both sintering and HIPing with the Eu partitioning factor of 23 between ceramics and the residual glass are suitable waste forms for minor actinides with processing chemicals. Abstract : Glass‐ceramics with internally crystallized major Eu2 Ti2 O7 pyrochlore and minor Eu4.67 O(SiO4 )3 apatite as potential waste forms for minor actinides have been fabricated via both sintering and hot isostatic pressing of a mixed oxide precursors at 1200°C. The phase formation, structures, microstructures, and chemical durability have been investigated.